Physical Activities among Diabetic Patients Attending Diabetic Centers in Kurdistan Region, Iraq - Jawdat Mamand Alhagbaker; Sideeq Sadir Ali; Bekhal Saber Ahmed (Hawler Medical University, 2020)
Background and objective: Physical activity is defined as basic public health for the human body and one of the main treatments for many chronic diseases, especially diabetes mellitus. The aim of this study to assess the level of physical activity among diabetic patients in Kurdistan and determine the association between levels of physical activity and certain variables of socio-demographic and clinical data. Methods: This cross-sectional study was conducted on 444 diabetes patients in the Kurdistan region of Iraq. The data was collected from 20th June to 10th September 2018 through interviews by using a questionnaire checklist. The data was analyzed by using the statistical package for the social sciences program. Results: Nearly half of the participants (49.1%) were middle-aged (36 - 55 years). Majority of them were females (65.1%), married (88.1%) and illiterate (42.3%). Nearly half of them (43.9%) were obese, having high blood glucose levels (76.8%) and half of them (50%) had hypertension. Majority (75.5%) of participants were within high levels of physical activity. A highly significant relationship was found between the level of physical activity and sex (P-value < 0.001), presence other chronic diseases, hypertension and heart disease. There were significant relationships between the body mass index and diagnostic duration of diabetes mellitus with the presence of other chronic diseases, presence hypertension, and heart disease. Conclusion: The majority of diabetic patients had high levels of physical activity, high blood sugar levels, obese, and had many chronic diseases. There was a statistically significant association between the level of physical activity with some variables of socio-demographic and clinical data. There was a highly significant association between body mass index and diagnostic duration of diabetes mellitus with the presence of other chronic disease.